Exposure to environmental toxicants and gout risk in adults: Unveiling the associations and potential targets - Xinglin Wan; Yapei Sun; Haoyu Mao; Xin Han; Jie Zhou; Weixia Duan; Cong Liu; Tao Li; Min Qian; Qin Yu; Shangcheng Xu (Ecotoxicology and Environmental Safety)
Emerging environmental toxicants may jeopardise uric acid metabolism, but the associations between toxicants and gout risk remain unknown. This study aimed to comprehensively assess the associations of toxicants with gout and to investigate the mediated mechanisms. This cross-sectional study included 22,591 adults diagnosed with gout in the NHANES 2011–2018. Twenty-one toxicants in 5 categories were detected in the blood, including acrylamide, ethylene oxide, metals, nicotine metabolites, and polyfluoroalkyl substances (PFAS). Multivariate logistic regression analyses were used to assess the associations of toxicant exposures with gout risk. Moreover, this study performed enrichment analysis and protein network analysis to identify potential hub targets of toxicants. Among the 22,591 participants aged 49.8 ± 17.8 years and 1082 (4.8 %) were diagnosed with gout. In the weighted logistic regression, Cu, Pb, Hg, and PFNA were positively associated with gout risk. The E-R curves revealed the linear relationships of Cu, Pb, Hg, and PFNA with gout risk without a safe threshold. Significant mediating effects of liver function, eGFR, and OBS were observed in the relationships of Cu, Pb, and Hg with gout risk. Moreover, network toxicology analyses revealed that TNF and AKT1 are shared hub targets of Cu, Pb, Hg, and PFNA. Our study indicated that elevated oxidative levels and decreased liver and kidney functions posed a crucial mediating effect on the associations between toxicants and gout risk. TNF and PI3K-Akt signalling pathways may be shared mechanisms of the adverse effects of toxicants on gout.